2016
DOI: 10.18805/ijar.v0iof.4553
|View full text |Cite
|
Sign up to set email alerts
|

Detection of osteopontin transcript in seminal plasma and its association with post-freeze-thaw quality of cryopreserved spermatozoa in mithun (Bos frontalis)

Abstract: The study aimed to detect osteopontin (OPN) transcript in seminal plasma and to assess the relationship between the presence of the transcript and post-freeze-thaw quality of cryopreserved spermatozoa in mithun (Bos frontalis). Semen samples were collected from five adult bulls through rectal massage method and cryopreserved in tris-egg yolk-glycerol extender. OPN transcript was detected by RT-PCR in the RNA purified from seminal plasma. OPN transcript was found to be present consistently in three animals (OPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Erikson (2006) conducted in vitro studies but could not establish any direct relationship between the OPN concentration and morphological aspects of sperms. Significant positive correlation between OPN level and the percentage of plasma membrane intact spermatozoa were in accordance with the findings of Baruah et al (2017) that documented the role of OPN in stabilizing the sperm plasma membrane and resist damages occurring during cryopreservation process. Highly significant positive correlation between OPN level and the percentage of acrosomal intact spermatozoa simulate the findings of Cancel et al (1999) who stated that the amount of OPN was more in acrosomal intact spermatozoa and vice versa.…”
Section: Antioxidant Enzymessupporting
confidence: 89%
“…Erikson (2006) conducted in vitro studies but could not establish any direct relationship between the OPN concentration and morphological aspects of sperms. Significant positive correlation between OPN level and the percentage of plasma membrane intact spermatozoa were in accordance with the findings of Baruah et al (2017) that documented the role of OPN in stabilizing the sperm plasma membrane and resist damages occurring during cryopreservation process. Highly significant positive correlation between OPN level and the percentage of acrosomal intact spermatozoa simulate the findings of Cancel et al (1999) who stated that the amount of OPN was more in acrosomal intact spermatozoa and vice versa.…”
Section: Antioxidant Enzymessupporting
confidence: 89%
“…Research on mithun has shown the essential role of OPN in membrane stability. It results in a better resistance of spermatozoa to cryopreservation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The osteopontin (OPN) gene is one of the genes studied. However, research on banteng spermatozoa is still limited and uses conventional approaches [ 20 , 21 ]. Osteopontin is synthesized by the ampullary accessory gland epithelial cells [ 22 ], and it is present in seminal plasma and is associated with the freezing ability of bovine semen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in stallions have shown positive effects of higher levels of OPN in seminal plasma on fertility. Additionally, research conducted by Baruah et al [29] highlighted the significant role of OPN in the cryopreservation process. In their study, OPN levels were positively correlated with various sperm characteristics.…”
Section: Comparative İnsights Of Opn On Fertility In Other Speciesmentioning
confidence: 99%